ANALISIS RASIO RGEC SEBAGAI INDIKATOR PENILAIAN TINGKAT KESEHATAN BANK DENGAN PENDEKATAN RBBR - Hellamida Fanureka; Maslichah Maslichah; M. Cholid Mawardi (e_Jurnal Ilmiah Riset Akuntansi, 2020)
This study aims to determine the soundness of state-owned commercial banks in the 2016-2018 period using the RGEC (Risk Profile, Good Corporate Governance, Eranings, and Capital) ratio with the RBBR (Risk Based-Bank Rating) approach.            This type of research is a quantitative descriptive study. The population in this study is state-owned commercial banks listed on the Indonesia Stock Exchange (IDX), while the samples used are 4 state-owned commercial banks using purposive sampling techniques. The data analysis technique is in the form of an analysis using the RBBR (Risk Based-Bank Ratio) approach with the RGEC ratio as the indicator.            The results of this study show that the average NPL value for 2016-2018 shows that state-owned banks have a very healthy predicate. While the average LDR value indicates that the bank is predicated fairly sound. Then the average value of GCG shows that the bank is healthy. Then the average earnings value shows that the bank is very healthy and the average capital value shows that the bank is very healthy.Keywords: Bank Health, BUMN Commercial Banks, RGEC Ratio.